Análisis de cambio de coberturas de la tierra durante el periodo 2000 – 2023 en el Parque Nacional Natural El Tuparro, departamento del Vichada, Colombia (2023)
This research shows the results obtained from a multitemporal analysis of the El Tuparro National Natural Park, located in the department of Vichada, Colombia, to determine the transformation of the land cover in this area. Using Landsat 7 and 8 imageries for the years 2000, 2013, and 2023 taken by remote sensing from the USGS Earth Explorer portal, a comparison of the change in the coverage was made and determining the area of the coverage present in the area that has been affected, for this a supervised classification is carried out in the study area. The classification of coverage during the periods analyzed is presented.